Knowledge, attitudes, and practices of cardiac rehabilitation and barriers to referral among cardiologists in Saudi Arabia: A cross-sectional survey - Ahmed Mohammed Almoghairi; Jane O’Brien; Anna Doubrovsky; Jed Duff (PLoS ONE, 2025)
Background Cardiac rehabilitation (CR) is an effective secondary prevention intervention, yet it is globally underutilized. Physicians play a key role in CR uptake by eligible patients through encouragement and referral to the program. This study assessed the knowledge, attitudes, and practices concerning CR among cardiologists in the Kingdom of Saudi Arabia (KSA), identified barriers to patient referrals to CR programs, and proposed strategies to increase service adoption. Methods We conducted an observational cross-sectional study in which an online questionnaire was distributed via email to cardiologists and cardiology fellows during the Saudi Heart Association’s annual conference in October 2023 and through social media platforms. Participants were required to have at least six months of clinical practice in managing patients, including those with coronary heart disease (CHD) following percutaneous coronary intervention (PCI). Results Of the 140 cardiologists surveyed, 106 completed more than 95% of the questionnaires. The cohort, which was primarily male (88.7%), included 67% consulting cardiologists, 15.1% fellows, and 17.9% specialists in areas such as general cardiology (29.2%), interventional cardiology (21.7%), and echocardiography (20.8%). Major barriers included a lack of local CR services (72.6%) and inadequate referral systems (41.5%). Despite the challenges and mixed views on the effectiveness of CR in KSA, attitudes toward CR were largely positive. The knowledge scores averaged 7.97, indicating a moderate to high understanding of CR services and benefits. Referral practices vary widely and are influenced by demographic and workplace factors, mainly geographic location. Conclusions While cardiologists in KSA generally have reasonable knowledge of CR and its benefits, substantial barriers hinder its broader implementation. There is enthusiasm for adopting diverse CR models; thus, further research is necessary to explore and evaluate alternative CR approaches, including home-based CR and telerehabilitation, to enhance patient care.